Regional monetary cooperation and growth-enhancing policies : the new challenges for Latin America and the Caribbean (UN New YorkUS, 2011)
Reviews the SUCRE initiative, proposal launched by the members of ALBA (Bolivia, Cuba, Ecuador, Honduras, Nicaragua and Venezuela), aimed at offering members a virual currency, to progressively replace the US dollar as the invoicing currency of intra-regional trade and permitting the use of domestic currencies of the member countries for final clearing and settlement. Concludes that this proposal should be accompanied by more intense efforts of policy coordination, particularly with respect to exchange and interest rates, in order to achieve the expected outcomes in terms of trade, growth and employment.
Keywords: ECONOMIC COOPERATION